Is the use of hormonal contraception a risk factor for incident sexually transmitted infections in a cohort of women aged 18 to 35 in Soweto, South Africa? - Moyes, Jocelyn Anstie (My University, 2010)
Introduction This secondary data analysis of a prospective cohort study set out to describe the association between the use of hormonal contraception and sexually transmitted infection (STI) acquisition in a cohort of 752 HIV negative women who were followed up for a year. Methods Outcome variables were measured by standard laboratory tests (PCR for Chlamydia trachomatis (CT) and Neiserria gonorrhoea (NG), culture for Trichomonas vaginalis (TV) and gram stain with Nugent score for Bacterial Vaginosis (BV). Exposure variable information was collected by structured interview. Basic descriptive statistics were applied to describe the characteristics of the cohort, including a comparison of women who used contraception and those who did not. A time series analysis including incidence rates for the outcomes (CT, NG, TV and BV), Kaplan Meier curves for time to event measurement and Cox regression models (univariate and multivariate), for the estimation of risk were applied. Results The analysis found no significant difference between women who use hormonal contraception and those who did not with respect to baseline demographic characteristics. Incidence rates per 100 women years to follow up with 95% confidence intervals were: CT 13 (7 to 17), NG 2 (1 to 4), TV 6 (4 to10), BV 72 (63 to 83). Kaplan Meier curves showed no significant difference in time to event between women who used contraception and those who did not. Adjusted hazard ratios for women who used contraception was 1.12 (0.69 to1.82) for CT, 0.47 (0.17 to 1.30) for NG, 1.06 (0.48 to 2.34) for TV and 0.27 (0.05 to 1.52) for BV. Conclusion This analysis did not reveal any significant associations between the use of hormonal contraception and the acquisition of STIs, however the trends in risks follow those reported in the literature.
MSc (Med), Epidemiology and Biostatistics, University of the Witwatersrand
Keywords: sexually transmitted diseases; women; risk factors; hormonal contraception